A Statistical study on Baguio Oil - Guanio, Terence; Ofrecio, Leandro; Sabado, Jorge (Diliman, Quezon City College of Engineering, 2001)
In any manufacturing concern, information about the factors, which affect the rejection of the product of concern is always a necessary component in the optimization of production. This study provides an initial look into the factors, which affect the rejection of the refined oil produced by Baguio Oil. The study was carried out with three primary concerns, 1) Understanding of the process. 2) Identifying factors affecting rejection and 3) Verifying the effect of the identified factors on the rejection parameter. The group identified and Bleaching and Deodorizing tanks used as factors affecting the percent FFA of the oil. The study was then divided into two single factor experiments based on the Fixed-effects model. With the use of the analysis of variance method the group was able to come up with the conclusion that the said factors have no effect on the percent FFA of the oil. Further statistical analysis done on the data showed that the power of the tests were low and thus the group recommended that a further studies be made with the introduction of new factors so that an appropriate model of the experiment can be obtained.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 28 : Statistical Analysis for Industrial Engineering
Keywords: Statistics